Modelling and visualizing the spatial patterns in access mode choice and the potential for bicycle in access trips in Rio de Janeiro - Souza, Flavia Carvalho de (2017)
The present study presents statistical models which identify the main factors affecting access mode choice and the barriers and motivators for the use of bicycle in integration with public transport. Additionally, this study enables the visualization of the spatial patterns of both access mode choice and the potential for bicycle in access trips. Some results are in line with studies conducted in other countries, but also other results show some particularities from the local context.